Growth Factors, Their Receptor Expression and Markers for Proliferation of Endothelial and Neoplastic Cells in Human Osteosarcoma. (July 2013) - Bianchi, E.; Artico, M.; Di Cristofano, C.; Leopizzi, M.; Taurone, S.; Pucci, M.; Gobbi, P.; Mignini, F.; Petrozza, V.; Pindinello, I.; Conconi, M.T.; Della Rocca, C.
Osteosarcoma is the most common primary malignant tumour of the bone. Although new therapies continue to be reported, osteosarcoma-related morbidity and mortality remain high. Modern medicine has greatly increased knowledge of the physiopathology of this neoplasm. Novel targets for drug development may be identified through an understanding of the normal molecular processes that are deeply modified in pathological conditions. The aim of the present study is to investigate, by immunohistochemistry, the localisation of different growth factors and of the proliferative marker Ki-67 in order to determine whether these factors are involved in the transformation of osteogenic cells and in the development of human osteosarcoma. We observed a general positivity for NGF — TrKA — NT3 — TrKC — VEGF in the cytoplasm of neoplastic cells and a strong expression for NT4 in the nuclear compartment. TGF-p was strongly expressed in the extracellular matrix and vascular endothelium. BDNF and TrKB showed a strong immunolabeling in the extracellular matrix. Ki-67/MIB-1 was moderately expressed in the nucleus of neoplastic cells. We believe that these growth factors may be considered potential therapeutic targets in the treatment of osteosarcoma, although proof of this hypothesis requires further investigation.